(untitled) (Modern education and development, 2025)
This article criticizes the concept of meritocracy in modern life. Meritocracy — the system in which people’s achievement is solely based on their merits, in other words, individuals ‘’earn what they get‘’ in society and their social status reflects what they have done and contributed. However, this system is not fair to everyone, as it ignores people’s backgrounds and unequal opportunities that some groups of people can have from birth. This article explores how factors like social class, access to high- quality education, and nepotism can outweigh merit, leading to unfair results despite individuals are making equal efforts. The paper begins by explaining the basic idea of the meritocracy and then compares this social belief to the real barriers that can be faced by many people from disadvantaged backgrounds including limited access to prestigious education. Special attention is given to the nepotism, a clear contrasted idea that is about prioritizing personal connection over merit. Throughout the article, the author will explain how privilege plays a major role in one’s success across most of the fields using real-world cases. Hard work matters; it is an undeniable fact, but it is not always enough in a system where someone’s start line is another person’s 2-3 year effort. The article concludes with an emphasize on the need to redefine the term success, taking into consideration systematic inequality. Because it is the only way that societies can move forward is a model where merit pays off. This work adds to wider academic discussions on social fairness, access, and the viability of performance-based systems.